2016
DOI: 10.1039/c6mt00167j
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Fe–S proteins: definition of a consensus motif recognized by the co-chaperone HSC20

Abstract: Iron-sulfur (Fe-S) clusters are inorganic cofactors that are fundamental to several biological processes in all three kingdoms of life. In most organisms, Fe-S clusters are initially assembled on a scaffold protein, ISCU, and subsequently transferred to target proteins or to intermediate carriers by a dedicated chaperone/co-chaperone system. The delivery of assembled Fe-S clusters to recipient proteins is a crucial step in the biogenesis of Fe-S proteins, and, in mammals, it relies on the activity of a multipr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 172 publications
2
38
0
Order By: Relevance
“…Likewise, the mutant protein is unable to receive a [2Fe-2S] cluster from typical iron-sulfur scaffold proteins such as Isa1 and IscU (Table 5), which have been shown to deliver a cluster into native NFU1 [10, 14]. Current models for Fe/S cluster biogenesis indicate that transfer from IscU is promoted with assistance from heat shock chaperone proteins [16, 37, 47, 55]. We have found that transfer from holo IscU to apo native NFU1 or G208C NFU1 does not occur in the presence of the chaperones (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, the mutant protein is unable to receive a [2Fe-2S] cluster from typical iron-sulfur scaffold proteins such as Isa1 and IscU (Table 5), which have been shown to deliver a cluster into native NFU1 [10, 14]. Current models for Fe/S cluster biogenesis indicate that transfer from IscU is promoted with assistance from heat shock chaperone proteins [16, 37, 47, 55]. We have found that transfer from holo IscU to apo native NFU1 or G208C NFU1 does not occur in the presence of the chaperones (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…5B), indicating that human IscU is incapable of transferring cluster into G208C NFU1 (data not shown). Because involvement by Hsc co-chaperones has been implicated in IscU-promoted cluster delivery to target proteins [16, 37, 47], we also examined the kinetics of transfer from holo human IscU to apo human NFU1 and G208C NFU1 in the presence of HSPA9, Hsc20, MgCl 2 and ATP. With the chaperones, IscU was unable to transfer cluster in to either the native or the mutant (Fig.…”
Section: Functional Impairment Of G208c Nfu1mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some Fe-S clusters are deeply buried within proteins, suggesting that they must be inserted during folding, and in some cases, they may contribute to the tertiary structure of the protein, by drawing distal cysteine residues into proximity (75,76).…”
Section: How Are Fe-s Clusters Delivered To Correct Recipient Proteins?mentioning
confidence: 99%
“…If Fe-S proteins prove to be fairly abundant, it would affect the calculations about cysteines, disulfide bonds, and redox status, as many cysteines would be engaged in ligating Fe-S cofactors (98). Bioinformatics approaches can foster identification of candidate Fe-S proteins, in combination with sophisticated biochemical techniques that enable researchers to study these labile prosthetic groups under protected conditions (75).…”
Section: How Are Fe-s Clusters Delivered To Correct Recipient Proteins?mentioning
confidence: 99%